2016
DOI: 10.1021/acs.chemrev.5b00676
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effects on Asymmetric Catalysis

Abstract: This review highlights a number of additives that can be used to make asymmetric reactions perfect. Without changing other reaction conditions, simply adding additives can lead to improved asymmetric catalysis, such as reduced reaction time, improved yield, or/and increased selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
194
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(201 citation statements)
references
References 687 publications
(799 reference statements)
6
194
1
Order By: Relevance
“…Intriguingly, the diamine 4e has been overlooked as a chiral ligand for over a decade despite its potential utility and simplicity42. We finally found that diisopropylamine ( i Pr 2 NH: 10 mol%) can further improve not only the reactivity, but also the enantioselectivity43, affording (1 R ,2 R ,10b S )- 3aa in 71% yield, >50/1 d.r. and 91% e.e., with 5 mol% of Ni(OAc) 2 ·4H 2 O–( R,R )- 4e (Table 1, entry 14).…”
Section: Resultsmentioning
confidence: 91%
“…Intriguingly, the diamine 4e has been overlooked as a chiral ligand for over a decade despite its potential utility and simplicity42. We finally found that diisopropylamine ( i Pr 2 NH: 10 mol%) can further improve not only the reactivity, but also the enantioselectivity43, affording (1 R ,2 R ,10b S )- 3aa in 71% yield, >50/1 d.r. and 91% e.e., with 5 mol% of Ni(OAc) 2 ·4H 2 O–( R,R )- 4e (Table 1, entry 14).…”
Section: Resultsmentioning
confidence: 91%
“…The variation of stereoselection with the nature of the counterion, which is dependent on the acid used as co-catalyst is a very well known act in organocatalytic transformations. 21 The acid additive accelerates the formation of iminium ion, and in the present case the drop in the enantioselection could be attributed to the extension in which the uncatalyzed background cyclization occurs.…”
mentioning
confidence: 50%
“…Further investigation of various additives 40 showed the beneficial effect of MS13X on the reactivity and selectivities (entries 9–13). As other additives such as MS3A and 4A afforded lower yields, MS13X is less likely to serve as a simple desiccant in this case ( vide infra ).…”
Section: Resultsmentioning
confidence: 99%